Klasifikasi Customer Intent untuk Mengetahui Tingkat Kepuasan Pelanggan menggunakan Metode Support Vector Machine pada Restoran Bakso President - Julia Ferlin; Fitra Abdurrachman Bachtiar; Alfi Nur Rusydi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The number of Bakso restaurants in Malang require Bakso President to improve business strategies to maintain or increase customer satisfaction. Intent classification is one way to assist Bakso President in categorizing customer intent as supporting information in generating business strategy or decisions. Customer intent itself is the desire or intention of the customer on a certain product or service. This study classifies customer intent based on 2252 reviews data written by customers on the TripAdvisor and Google Review sites then classified according to 3 categories of customer intent, namely quit, direct, complaint intent, and